The Co-occurrence of NDM-5, MCR-1, and FosA3-Encoding Plasmids Contributed to the Generation of Extensively Drug-Resistant Klebsiella pneumoniae - Zhou, Ying; Ai, Wenxiu; Cao, Yanhua; Guo, Yinjuan; Wu, Xiaocui; Wang, Bingjie; Rao, Lulin; Xu, Yanlei; Zhao, Huilin; Wang, Xinyi; Yu, Fangyou (Frontiers in Microbiology, 2022)
The rise and global dissemination of extensively drug-resistant (XDR) bacteria are often related to plasmid-borne mobile antimicrobial resistance genes. Notably, isolates having multiple plasmids are often highly resistant to almost all the antibiotics available. In this study, we characterized an extensively drug-resistant Klebsiella pneumoniae 1678, which exhibited high-level resistance to almost all the available antibiotics. Through whole-genome sequencing (WGS), more than 20 resistant elements and 5 resistant plasmids were observed. Notably, the tigecycline resistance of K. pneumoniae 1678 was not related to the plasmid-borne tetA gene but associated with the overexpression of AcrAB and OqxAB efflux pumps, according to the susceptibility results of tetA-transformant and the related mRNA quantification of RND efflux pumps. Except for tigecycline resistance, three plasmids, mediating resistance to colistin, Fosfomycin, and ceftazidime–avibactam, respectively, were focused. Detailed comparative genetic analysis showed that all these plasmids belonged to dominated epidemic plasmids, and harbored completed conjugation systems. Results of conjugation assay indicated that these three plasmids not only could transfer to E. coli J53 with high conjugation frequencies, respectively, but also could co-transfer to E. coli J53 effectively, which was additionally confirmed by the S1-PFGE plasmids profile. Moreover, multiple insertion sequences (IS) and transposons (Tn) were also found surrounding the vital resistant genes, which may form several novel mechanisms involved in the resistant determinants’ mobilization. Overall, we characterized and reported the uncommon co-existence and co-transferring of FosA3-, NDM-5, and MCR-1-encoding plasmids in a K. pneumoniae isolate, which may increase the risk of spread of these resistant phenotypes and needing great concern.